Fostering legal equality: collaborative program by UiTMLaw Legal Aid CIinic and Malaysian legal Aid Department - UiTM, Faculty of Law (Faculty of Law, 2023)
The UiTMLaw Legal Aid Clinic (LAC) has organized a program in collaboration with the Malaysian Legal Aid Department (JBG) titled 'Pro Bono Gateway to Fairness' for the eligible. The Tile program was held on May 17, 2023, at the Faculty of Law, Universiti Teknologi MARA, and it was presented by Ms. Ani Nadirs Abu Bakar, Deputy Senior Director of the Legal Aid Department, and Mr. Nuraswan Aminuddin, Director of the Panel Lawyers and Legal Counsel Division. The program was also inaugurated by Ms. Siti Salwa bin Mohd Nor@Ghazali, Director of Mediation (Sharia) at the Legal Aid Department. The program was organized to share accurate and precise information about the role and functions of the Legal Aid Department as a leader in legal aid services to provide access to justice in general. The program also aimed to provide exposure and enlightenment regarding the services offered by the Legal Aid Department in delivering professional-quality legal aid services to eligible individuals to ensure access to justice.